A cross sectional study on knowledge, attitude and practice of family planning method usage among urban women of Dr. B. R. Ambedkar Medical College field practice area - Devaru, Jagadish S.; Jabeen, Bushra; Mayanna, Puttaswamy (International Journal Of Community Medicine And Public Health, 2020)
Background: India is currently facing “population explosion” which is directly perpetuating development of country. Family planning is the only safest and cost-effective strategies to have impact on health of women. Methods: Community based cross sectional study, conducted by face to face interview with women included for study after systematic random sampling. The collected information was analysed using appropriate statistical tools. Results: Total of 88.7% of women were aware that family planning is for limitation of births but, 292 (70.2%) women had ever used contraceptive, and 30 (24.2%) of them have faced minor complications, which has either self-resolved or on medication. The most common reason for not using contraceptive was being uncomfortable (76.6%) to use them. Conclusions: Women had good knowledge regarding contraceptives, but most of the women followed methods suggested by their elders. Advertisement regarding newer methods has to be strengthened.